Furo[3,4-b]chromones, and not Pyrano[3,4-b]chromones, are Obtained by the Reaction of 3-Formylchromones with Isocyanides - Neo, Ana G.; Garrido, Leda; Díaz, Jesús; Marcaccini, Stefano; Marcos, Carlos F. (Synlett, 2012)
The reaction of formylchromones with alkyl isocyanides was reinvestigated. In earlier reports from other research groups, two different structures were proposed for the products of this reaction. Herein, we provide unambiguous evidence that these products are chromenylmethylene furochromenones and not pyranochromones. Our structure assignment is based on X-ray diffraction analysis and two-dimensional NMR methods. The knowledge of the correct structure of these compounds is essential for the design of derivatives with potential applications as bioactive molecules or fluorescent biomarkers.
Keywords: cycloaddition reactions; furans; fused-ring systems; multicomponent reactions; heterocycles; natural products